Loss of SUSD2 expression correlates with poor prognosis in patients with surgically resected lung adenocarcinoma - Guo, Wei (J Cancer, 2020)
There is limited evidence regarding the relationship between the expression of Sushi Domain Containing 2 (SUSD2) and prognosis of patients with surgically resected lung adenocarcinoma (LUAD). This retrospective study aimed to investigate the clinical significance of SUSD2 expression in LUAD. To assess SUSD2 expression in LUAD, we conducted both integrated bioinformatic analysis based on the TCGA database and also immunohistochemistry study using a tissue microarray encompassing 578 LUAD cases from our hospital. Reduced SUSD2 expression was associated with gender, smoking history, higher pathological grade, lymph node metastasis, larger tumor length, advanced TNM stage. LUAD patients with SUSD2-positive tumors showed significantly better overall survival (OS) than those with SUSD2-negative tumors (P = 0.000). When patients were stratified into those with stage I (218, 37.7%), II (152, 26.3%) and III (208, 36.0%) disease, and those without (254, 43.9%) and with (324, 56.1%) lymph node metastasis, the prognostic effect was almost consistent. The OS of patients with positive SUSD2 expression was significantly better in patients with stage I (P = 0.000), III (P = 0.000), without (P = 0.000) and with (P = 0.001) lymph node metastasis. Multivariate analysis showed that loss of SUSD2 predicted a shorter survival time and was an independent prognostic factor for LUAD patients. Our study indicated that SUSD2 may serve as a new prognostic and potential therapeutic target in LUAD.